2018
DOI: 10.1016/j.bone.2017.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolism in bone

Abstract: The adult human skeleton is a multifunctional organ undergoing constant remodeling through the opposing activities of the bone-resorbing osteoclast and the bone-forming osteoblast. The exquisite balance between bone resorption and bone formation is responsible for bone homeostasis in healthy adults. However, evidence has emerged that such a balance is likely disrupted in diabetes where systemic glucose metabolism is dysregulated, resulting in increased bone frailty and osteoporotic fractures. These findings th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(121 citation statements)
references
References 84 publications
3
115
0
3
Order By: Relevance
“…Recent studies have elucidated the role of glucose metabolism in maintaining bone homeostasis. It has been shown that glucose metabolism is required for osteoblast and osteoclast differentiation, as well as for cell‐type–specific processes including matrix deposition and resorption . In order to assess the impact of MCT4 deletion on vertebral bone health, we compared the cortical and trabecular bone morphology in the caudal and lumbar vertebrae from 14‐month‐old WT and MCT4 KO mice using μCT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have elucidated the role of glucose metabolism in maintaining bone homeostasis. It has been shown that glucose metabolism is required for osteoblast and osteoclast differentiation, as well as for cell‐type–specific processes including matrix deposition and resorption . In order to assess the impact of MCT4 deletion on vertebral bone health, we compared the cortical and trabecular bone morphology in the caudal and lumbar vertebrae from 14‐month‐old WT and MCT4 KO mice using μCT.…”
Section: Resultsmentioning
confidence: 99%
“…One interpretation of these results is that glucose metabolism is affected in the resident trabecular bone cells: the osteoblasts and osteoclasts. Although the effect of lactate accumulation in these cells has not been studied in detail, it is known that they rely on glucose uptake for cell differentiation and bone formation . In fact, recent studies showed that osteoblasts preferentially use glycolysis for ATP production, even under aerobic conditions, mimicking the Warburg effect .…”
Section: Discussionmentioning
confidence: 99%
“…Glucose metabolism in the skeleton under physiological and pathological conditions has been deeply scrutinized . Unlike classical glucose‐handling organs such as muscle, liver and white adipose tissue, aerobic glycolysis is the major pathway for the utilization of glucose by the skeleton .…”
Section: Bone As An Insulin Target Organ and Its Role In Glucose Homementioning
confidence: 99%
“…Osteoclasts are well established as being rich in mitochondria; osteoclastic bone resorption normally proceeds much more rapidly than osteoblastic bone formation, and its requirement for energy is, presumably, high . However, no data are available regarding how much glucose osteoclasts take up to perform their activities.…”
Section: Unmet Needsmentioning
confidence: 99%
See 1 more Smart Citation